Lysosomal and phagocytic activity is increased in astrocytes during disease progression in the SOD1 G93A mouse model of amyotrophic lateral sclerosis - Baker, David J.; Blackburn, Daniel J.; Keatinge, Marcus; Sokhi, Dilraj; Viskaitis, Paulius; Heath, Paul R.; Ferraiuolo, Laura; Kirby, Janine; Shaw, Pamela J. (Frontiers in Cellular Neuroscience, 2015)
Astrocytes are key players in the progression of amyotrophic lateral sclerosis (ALS). Previously, gene expression profiling of astrocytes from the pre-symptomatic stage of the SOD1G93A model of ALS has revealed reduced lactate metabolism and altered trophic support. Here, we have performed microarray analysis of symptomatic and late-stage disease astrocytes isolated by laser capture microdissection (LCM) from the lumbar spinal cord of the SOD1G93A mouse to complete the picture of astrocyte behaviour throughout the disease course. Astrocytes at symptomatic and late-stage disease show a distinct up-regulation of transcripts defining a reactive phenotype, such as those involved in the lysosome and phagocytic pathways. Functional analysis of hexosaminidase B enzyme activity in the spinal cord and of astrocyte phagocytic ability has demonstrated a significant increase in lysosomal enzyme activity and phagocytic activity in SOD1G93A vs. littermate controls, validating the findings of the microarray study. In addition to the increased reactivity seen at both stages, astrocytes from late-stage disease showed decreased expression of many transcripts involved in cholesterol homeostasis and decreased cholesterol synthesis has been confirmed in vitro. Staining for the master regulator of cholesterol synthesis, SREBP2, has revealed an increased localisation to the cytoplasm of motor neurons in late-stage SOD1G93A spinal cord, indicating that motor neurons may attempt to synthesise their own cholesterol in response to decreased astrocytic cholesterol provision. Our data reveal that SOD1G93A astrocytes are characterised more by a loss of supportive function than a toxic phenotype during ALS disease progression and future studies should focus upon restorative therapies.